2015
DOI: 10.1128/aac.00581-15
|View full text |Cite
|
Sign up to set email alerts
|

Superior Serum Concentrations with Posaconazole Delayed-Release Tablets Compared to Suspension Formulation in Hematological Malignancies

Abstract: d Posaconazole (PCZ), approved for prophylaxis against invasive fungal disease in high-risk patients, is commercially available orally as a suspension formulation (PCZ-susp) and as a delayed-release tablet (PCZ-tab). We evaluated the serum steady-state concentrations (C ss ) of PCZ stratified by the administered formulation for antifungal prophylaxis in patients with myeloid malignancies (n ‫؍‬ 150). The primary outcome was the attainment rate of the target C ss of >700 ng/ml. Secondary outcomes included toxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
47
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 15 publications
11
47
2
Order By: Relevance
“…PCZ was associated with a rate of proven or probable breakthrough IFIs of only 2%, which was comparable to the low rates of breakthrough infections seen in registry and real-life data with both the PCZ suspension and PCZ tablets (2,15). The types of organisms implicated in the breakthrough IFIs were few in number and representative of the types of pathogens typically seen in high-risk hematological malignancy patients.…”
Section: Discussionmentioning
confidence: 61%
“…PCZ was associated with a rate of proven or probable breakthrough IFIs of only 2%, which was comparable to the low rates of breakthrough infections seen in registry and real-life data with both the PCZ suspension and PCZ tablets (2,15). The types of organisms implicated in the breakthrough IFIs were few in number and representative of the types of pathogens typically seen in high-risk hematological malignancy patients.…”
Section: Discussionmentioning
confidence: 61%
“…Although central nervous system (CNS) toxicity has not previously been reported with posaconazole, this observation may reflect the low levels achieved with the oral suspension combined with its low CNS penetration (7,10). However, newer formulations result in significantly higher posaconazole concentrations in serum (11), particularly in patients with low body mass (12). Use of posaconazole tablets can result in serum concentrations above the range that has been well …”
mentioning
confidence: 75%
“…39,40 The delayed release oral tablet is considered a more reliable option for the prophylaxis or treatment of IFIs. Studies have suggested that the posaconazole oral tablet has higher azole plasma levels 41 , better absorption 42 , and improved bioavailability 43 than that of oral suspension. Furthermore, an intravenous formulation of posaconazole was developed and FDA-approved in 2014 for patients who are unable to take oral medications.…”
Section: Second Generation Triazoles: Voriconazole and Posaconazolementioning
confidence: 99%